2017
DOI: 10.1038/pr.2017.197
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics affect the response to ketamine and opioids during the treatment of vaso-occlusive episode-related pain in sickle cell disease

Abstract: BackgroundN-methyl-D-aspartate receptor activation has been implicated in the pathobiology of inflammatory, nociceptive and neuropathic pain, opioid tolerance, opioid-induced hyperalgesia, and central sensitization. Some of those mechanisms underlie sickle cell disease(SCD)-associated pain.MethodsWe conducted an exploratory cohort study of SCD patients who during vaso-occlusive episodes (VOEs) received subanesthetic doses of the N-methyl-D-aspartate receptor antagonist, ketamine, as an adjunct to opioids. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…An important question is whether targeting those mechanisms that contribute to the development and maintenance of sensitization will be beneficial for managing pain in SCD. Activation of NMDA receptors in the spinal cord is an essential step in initiating and maintaining central sensitization [111] and it was reported that subanesthetic doses of ketamine, a noncompetitive NMDA receptor antagonist, given as an adjunct to opioids for vaso-occlusive episodes, reduced pain and opioid consumption [112]. Targeting mediators of neuroinflammation, such as prostaglandins, or administration of cytokine inhibitors or endogenous mediators that play a role in the resolution of inflammation, such as Resolvins which have been shown to reduce inflammation and organ damage in sickle mice [113], may be effective in managing pain in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…An important question is whether targeting those mechanisms that contribute to the development and maintenance of sensitization will be beneficial for managing pain in SCD. Activation of NMDA receptors in the spinal cord is an essential step in initiating and maintaining central sensitization [111] and it was reported that subanesthetic doses of ketamine, a noncompetitive NMDA receptor antagonist, given as an adjunct to opioids for vaso-occlusive episodes, reduced pain and opioid consumption [112]. Targeting mediators of neuroinflammation, such as prostaglandins, or administration of cytokine inhibitors or endogenous mediators that play a role in the resolution of inflammation, such as Resolvins which have been shown to reduce inflammation and organ damage in sickle mice [113], may be effective in managing pain in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Although early literature on ketamine use for VOE primarily consisted of case reports, [27][28][29][30][31][32][33] over the last three years, one randomized controlled trial (RCT) 34 and two cohort studies 28,35 have contributed to our knowledge of ketamine in this patient population. Coupled with previous cases, these studies will be instrumental in the creation of standardized ketamine use protocols.…”
Section: Patient Characteristics Including Age and Gendermentioning
confidence: 99%
“…Numerical pain rating scales are limited due to being a unidimensional assessment of pain at one moment in time in patient cohorts with dissimilar pain tolerance and medication response. [28] As noted by Nobrega et al [18] in their study of pediatric patients with sickle cell disease, there are significant inter-patient differences in response to LDKI; therefore, there may be a subset of patients more likely to benefit but not yet clearly delineated.…”
Section: Discussionmentioning
confidence: 98%
“…More important though, 47% of patients found LDKI to be "very helpful," which further argues that the objective response was real, at least for some of the patients. Nobrega et al [18] reported a meaningful reduction in pain scores in a large cohort of pediatric patients with sickle cell disease, but this was comparing baseline pain scores with pain scores taken after LDKI discontinuation, which was several days later and could be attributed to the natural improvement in patient symptoms. The two retrospective studies of patients with chronic pain reported improvement in pain scores immediately following LDKI which is the more pathophysiological expected time frame for response given the rapid onset of action of LDKI.…”
Section: Discussionmentioning
confidence: 99%